Cross-sectional comparison of body composition and resting metabolic rate in Premier League academy soccer players: Implications for growth and maturation - Hannon, M. P.; Carney, D. J.; Floyd, S.; Parker, L. J. F.; McKeown, J.; Drust, B.; Unnithan, V. B.; Close, G. L.; Morton, J. P. (Journal of Sports Sciences, 2020)
For the first time we aimed to: (1) assess fat-free mass (FFM) and RMR in youth soccer players, (2) compare measured RMR to estimated RMR using previously published prediction equations, and (3) develop a novel population-specific prediction equation. In a cross-sectional design, 99 males from a Premier League academy underwent assessments of body composition (DXA) and RMR (indirect-calorimetry). Measured RMR was compared to estimated values from five prediction equations. A novel RMR prediction equation was developed using stepwise multiple regression. FFM increased (P<0.05) between U12 (31.6±4.2 kg) and U16 (56.3±5.3 kg) after which no further increases occurred (P>0.05). RMR in the U12s (1655±195 kcal.day-1), U13s (1720±205 kcal.day-1) and U14s (1846±218kcal.day-1) was significantly lower than the U15s (1957±128 kcal.day-1), U16s (2042±155 kcal.day-1), U18s (1875±180 kcal.day-1) and U23s (1941±197 kcal.day-1) squads (P>0.05). FFM was the single best predictor of RMR (r2=0.43; P<0.01) and was subsequently included in the novel prediction equation: RMR (kcal.day-1) = 1315 + (11.1 x FFM in kg). Both FFM and RMR increase from 12-16 years old, thus highlighting the requirement to adjust daily energy intake to support growth and maturation. The novel prediction RMR equation developed may help to inform daily energy requirements.